On the Value of Faculty Development Abroad: Reflections on the 2000 Ghana Seminar Experience - Albert E. McCormick Jr.; Michelle McCormick (Journal of Public and Professional Sociology)
In the summer of 2000, we were part of a three-week faculty development seminar that travelled to the West African nation of Ghana. The seminar was sponsored and organized by the University System of Georgia African Council. The theme of the seminar was "Tradition and Modernity in Ghana."